2016
DOI: 10.1051/0004-6361/201526563
|View full text |Cite
|
Sign up to set email alerts
|

Ultramassive dense early-type galaxies: Velocity dispersions and number density evolution sincez= 1.6

Abstract: Aims. We investigate the stellar mass assembly history of ultramassive (M 10 11 M ) dense (Σ = M /2πR 2 e > 2500 M pc −2 ) early-type galaxies (ETGs, elliptical and spheroidal galaxies) selected on basis of visual classification over the last 9 Gyr. Methods. We traced the evolution of the comoving number density ρ of ultramassive dense ETGs and compared their structural (effective radius R e and stellar mass M ) and dynamical (velocity dispersion σ e ) parameters over the redshift range 0 < z < 1.6. We derived… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 117 publications
(231 reference statements)
5
26
0
Order By: Relevance
“…Damjanov et al (2015) found an almost constant number density over the redshift range 0.2< z <0.8 for colour selected passive compact galaxies with M > 8×10 10 M ⊙ . Gargiulo et al (2016) found ρ(z) ∝ (1 + z) 0.3±0.8 for a sample of morphologically selected elliptical dense galaxies (Σ 2500 M ⊙ pc −2 ) with M >10 11 M ⊙ in the redshift range 0 < z < 1.6, consistent with our results. Cassata et al (2013) found a very mild decrease of compact galaxies (1σ below the local SMR), and a mild increase in the number density of normal galaxies (consistent at 1σ with the local SMR) from z ∼ 1 to z ∼ 0.5, in qualitative agreement with our results.…”
Section: The Number Densities Of Mpgs In Vipers Field As a Function Osupporting
confidence: 91%
See 1 more Smart Citation
“…Damjanov et al (2015) found an almost constant number density over the redshift range 0.2< z <0.8 for colour selected passive compact galaxies with M > 8×10 10 M ⊙ . Gargiulo et al (2016) found ρ(z) ∝ (1 + z) 0.3±0.8 for a sample of morphologically selected elliptical dense galaxies (Σ 2500 M ⊙ pc −2 ) with M >10 11 M ⊙ in the redshift range 0 < z < 1.6, consistent with our results. Cassata et al (2013) found a very mild decrease of compact galaxies (1σ below the local SMR), and a mild increase in the number density of normal galaxies (consistent at 1σ with the local SMR) from z ∼ 1 to z ∼ 0.5, in qualitative agreement with our results.…”
Section: The Number Densities Of Mpgs In Vipers Field As a Function Osupporting
confidence: 91%
“…paper_I mass relation [SMR]), and in the rest-frame waveband used to derive the effective radius, make it difficult to compare results from different studies (or at different cosmic epochs, see e.g. Gargiulo et al 2016). Evidence shows that in conjunction with an increase in the mean radial size of PGs by a factor of ∼ 4 from z ∼ 1.5-2 to z = 0, the number of PGs per unit volume increases by a factor ∼ 10 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this reported precipitous decline in the number density is that quiescent compact galaxies somehow grow at intermediate redshifts. However, several studies examining dense regions in the local universe (Valentinuzzi et al 2010;Poggianti et al 2013) and quiescent galaxies at intermediate redshifts (Carollo et al 2013;Damjanov et al 2014Damjanov et al , 2015Gargiulo et al 2016) challenge these initial measurements of a rapid decline in the abundance of compact galaxy population at late times. These studies find that the number density of compact galaxies at z < 1 is nearly constant.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not the case. Indeed, the number density of ultramassive dense elliptical galaxies in the field seems to be constant over the redshift range 0.2 < z < 1.5 (Gargiulo et al 2016). This suggests that both the populations of high-mass elliptical galaxies, in cluster and in the field, are mostly formed at that redshift.…”
Section: Structural Properties Of Elliptical Galaxies In Cluster and mentioning
confidence: 99%
“…Actually, the definition of Σ R e here and commonly adopted does not take into account the presence of color gradients observed in most of the early-type galaxies at high redshift (e.g., Gargiulo et al 2011Gargiulo et al , 2012Guo et al 2011;Chan et al 2016, Ciocca et al 2016. Color gradients imply that the M/L is not radially constant and that, consequently, the stellar mass profile does not follow exactly the surface brightness profile.…”
Section: The Size-mass Relationmentioning
confidence: 99%